Evaluating Search Systems Using Result Page Context - Bailey, Peter; Craswell, Nick; White, Ryen W.; Chen, Liwei; Satyanarayana, Ashwin; Tahaghoghi, S. M. M. (3rd Symposium on Information Interaction in Context (IIiX 2010), New Brunswick, NJ, USA, 2010)
We introduce a method for evaluating the relevance of all visible components of a Web search results page, in the context of that results page. Contrary to Cranfield-style evaluation methods, our approach recognizes that a user's initial search interaction is with the result page produced by a search system, not the landing pages linked from it. Our key contribution is that the method allows us to investigate aspects of component relevance that are difficult or impossible to judge in isolation. Such contextual aspects include component-level information redundancy and cross-component coherence. We report on how the method complements traditional document relevance measurement and its support for comparative relevance assessment across multiple search engines. We also study possible issues with applying the method, including brand presentation effects, inter-judge agreement, and comparisons with document-based relevance judgments. Our findings show this is a useful method for evaluating the dominant user experience in interacting with search systems.
Best Paper Finalist